(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English The fact that a close relationship exist between farmlands and agricultural activities bring about a consequence that efforts for improving farmers welfare cannot be based only on technological and institutional improvement. The improvement in farmers’ access to farmlands will mostly determine the success of increasing the living standard of the rural society as a whole. The problem to be faced at present a however, that farmlands tend to be increasingly limited, due to competition with other uses of lands, whereas people working in the sector of agriculture is steadily, and absolutely increasing, resulting in an increasingly limited average proprietorship and control of land. This unfavourable condition could be attributed to the accumulated improper implementation of the development strategy which was not fully inclined to agriculture, by issuing various acts and regulations that enhance investors in having access to lands, including farmlands and lands under control of rural elders by tradition. Agrarian reform with the target to improve farmers’ access to farmlands should be commenced by reforming the aforementioned acts and regulations. This in turn should be accompanied by improving the data base related to the status of lands which is presently in a chaostic condition, due to the multiplicity of institution handling the problems related to land status, which has created the main obstacle in implementing the agrarian reform in Indonesia. A political commitment of the government and legislative institutions is urgently needed for this purpose. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian Eratnya keterkaitan lahan dengan kegiatan pertanian menyebabkan upaya perbaikan kesejahteraan petani tidak cukup hanya melalui perbaikan teknologi dan kelembagaan yang terkait dengan proses produksi, perbaikan akses petani terhadap lahan akan banyak menentukan keberhasilan upaya perbaikan kehidupan masyarakat pedesaan secara keseluruhan. Misalnya sekarang, lahan pertanian cenderung makin terbatas karena harus berkompetisi untuk berbagai penggunaan, sementara orang yang bekerja di pertanian secara absolut terus bertambah sehingga menyebabkan rata-rata pemilik dan penguasaan lahan semakin sempit. kondisi ini merupakan akibat dari akumulasi kesalahan di dalam penerapan kebijaksanaan pembangunan yang kurang berpihak pada pertanian, dengan dikeluarkannya sebagai undang-undang dan peraturan yang memudahkan investor untuk mendapatkan lahan, termasuk lahan pertanian dan hak ulayak masyarakat adat. Upaya reformasi agraria, dengan sasaran memperbaiki akses petani terhadap lahan, perlu di awali dengan mereformasi berbagai peraturan/perundangan yang ada. Upaya ini seharusnya dilakukan bersamaan dengan perbaikan terhadap basis data yang berkaitan dengan lahan, karena masih simpang-siurnya data dan banyaknya instansi yang menangani persoalan lahan, dan ini merupakan hambatan utama dalam pelaksanaan reformasi agraria di Indonesia. Agar upaya ini dapat terlaksanakan dibutuhkan political comitment dari pemerintah dan pihak legislatif tentang pentingnya reformasi agraria ini.